KAWASAN EKOWISATA PULAU PINUS DI KABUPATEN BANJAR - Aribah, Adzro; Sa’ud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The new normal disruption causes changes that change the behavior of the tourism landscape. These changes in tourism have made the trend of 'back to nature' travel safer and not cause additional additions. Therefore, tourism needs to consider the aspect of destruction. Therefore, the government and tourism-related institutions encourage sustainable tourism programs that involve three main aspects, namely environmental, social, and economic. Nature tourism has the potential to be developed into sustainable tourism by raising the concept of ecotourism. South Kalimantan has tourism with abundant natural resources that can be used as ecotourism such as the Pulau Pinus area. In the design of the Ecotourism of Pulau Pinus Area in Banjar Regency, a sustainable approach is used to support the Butterfly Effect design concept by making Pulau Pinus a sustainable tourism through sustainable development by applying materiality and zero waste to create efficiency and sustainable value.